An Adaptive Vestibular Rehabilitation Technique - Crane, Benjamin T. (Laryngoscope, 2017)
OBJECTIVES: There is a large variation in vestibular rehabilitation (VR) results depending on type of therapy, adherence, and the appropriateness for the patient’s level of function. A novel adaptive vestibular rehabilitation (AVR) program was developed and evaluated. STUDY TYPE: Technology and procedure development DESIGN: Prospective multi-center trial METHODS: Those with complete unilateral vestibular hypofunction (UVH) and symptomatic at least month with a dizziness handicap inventory (DHI)>30 were eligible. Patients were given a device to use with their own computer. They were instructed to use the program daily, with each session lasting about 10 minutes. The task consisted of reporting orientation of a letter C which appeared when their angular head velocity exceeded a threshold. The letter size and head velocity required were adjusted based on prior performance. Performance on the task was remotely collected by the investigator as well as a weekly DHI score. RESULTS: Four patients aged 31–74(mean 51) were enrolled in this feasibility study to demonstrate efficacy. Two had treated vestibular schwannomas and two had vestibular neuritis. Starting DHI was 32–56(mean 42) and reduced to 0–16(mean 11.5) after a month of therapy, a clinically and statistically significant (p<0.05) improvement. The three who continued therapy an additional month improved to a DHI of 4. CONCLUSION: This AVR method has advantages over traditional VR in terms of cost and customization for patient ability and obtained a major improvement in symptoms. This study demonstrated a clinically and statistically significant decrease in symptoms after 4 weeks of therapy. LEVEL OF EVIDENCE: 2b